Existence of Ampenan Port in the 19th Century (Maritime History Studies) - Masyitah, Putri Maya; Mubin, Ilmiawan; Mayasari SW, Dian Eka; Mu'aini, Mu'aini; Afandi, Ahmad; Rosada, Rosada (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to examine the activities of the Port of Ampenan as an important trading port on the island of Lombok in the 19th century. The method used in this study is the historical science research method which consists of gathering sources (heuristics), source criticism (verification), reasoning (interpretation) and writing (historiography). The concept used in this study is the port concept which examines ports from an economic standpoint, especially in terms of trade. The results showed that in the 19th century Ampenan Harbor was one of the active ports which became the center of shipping and trade on the island of Lombok. Around 1840 until the end of the 19th century, the Port of Ampenan was used as a center for trade activities between islands on the island of Lombok. The commodities traded are divided into two, namely commodities based on politics (rice, textiles, rifles, ammunition, opium, and liquor) and commodities based on needs (green beans, eggs, bird's nest, tobacco, tarum, cattle and horses, fish , wood sandalwood, sea cucumbers, turtles, and so on). Apart from being a local shipping and trade route, Ampenan Port is also included in international trade routes. There are several shipping companies that are active in shipping and trading at Ampenan Port, such as European, Chinese and Singaporean companies.